A dynamic model of the eye nystagmus response to high magnetic fields - Glover, Paul M; Li, Yan; Antunes, Andre; Mian, Omar S; Day, Brian L (Physics in medicine & biology, 2014)
It was recently shown that high magnetic fields evoke nystagmus in human subjects with functioning vestibular systems. The proposed mechanism involves interaction between ionic currents in the endolymph of the vestibular labyrinth and the static magnetic field. This results in a Lorentz force that causes endolymph flow to deflect the cupulae of the semi-circular canals to evoke a vestibular-ocular reflex (VOR). This should be analogous to stimulation by angular acceleration or caloric irrigation. We made measurements of nystagmus slow-phase velocities in healthy adults experiencing variable magnetic field profiles of up to 7 T while supine on a bed that could be moved smoothly into the bore of an MRI machine. The horizontal slow-phase velocity data were reliably modelled by a linear transfer function incorporating a low-pass term and a high-pass adaptation term. The adaptation time constant was estimated at 39.3 s from long exposure trials. When constrained to this value, the low-pass time constant was estimated at 13.6 ± 3.6 s (to 95% confidence) from both short and long exposure trials. This confidence interval overlaps with values obtained previously using angular acceleration and caloric stimulation. Hence it is compatible with endolymph flow causing a cupular deflection and therefore supports the hypothesis that the Lorentz force is a likely transduction mechanism of the magnetic field-evoked VOR.